Implementasi Metode SAW Terhadap Sistem Pendukung Keputusan Memilih Dosen Terbaik Pada Politeknik Ganesha - Romindo, Romindo (Politeknik Ganesha Medan, 2020)
The selection of the best lecturers gives recognition to lecturers who carry out tridharma higher education activities, whose results can be proud of and are useful for advancing academic and institutional quality. Educational institutions, especially the Ganesha Medan Polytechnic, annually select the best lecturers by conducting assessments by distributing questionnaires to their students. However, the assessment process is still done manually, so it takes a long time to process the data. In addition, the assessment is still not relevant to the actual situation because it only uses one assessment criterion, namely a student assessment questionnaire. Based on this, in this study, a decision support system design was used to select the best lecturers at the Ganesha Medan Polytechnic. Decision support systems built on a web basis using the PHP programming language and MySQL database. The decision making method used is the Simple Additive Weighting (SAW) method. This method is used to perform the best alternative ranking process from a number of alternatives.